Implementation of the Smoke-Free Area (SFA) Policy in Islamic University - Nahar, Syamsu; Ulfah, Fitria; Syam, Abdi Mubarrak; Siregar, Putra Apriadi; Suraya, Rani; Arrazy, Syafran (Public Health of Indonesia, 2025)
Background: Indonesia's high prevalence of active smoking among young adults, despite WHO recommendations, underscores the need for Smoke-Free Area (SFA) in educational institutions to promote healthier environments. Objective: This investigation aimed to evaluate adherence to Smoke-Free Area (SFA) regulations across three Islamic universities in Indonesia and analyze the associated tobacco use behaviours among students and faculty members. Methods: The study used a cross-sectional design, conducting structured interviews with 7.040 participants from Universitas Islam Negeri Sumatera Utara, Universitas Islam Negeri Syarif Hidayatullah Jakarta, and Universitas Islam Negeri Wali Songo Semarang. The research focuses on the dissemination of information about the dangers of smoking, designated smoking areas, and cigarette butts. The study used a structured questionnaire and JASP version 19 software for data analysis, including spatial analysis with QGIS. Results: Universitas Islam Negeri Sumatera Utara has the lowest overall compliance with regulations, while Universitas Islam Negeri Syarif Hidayatullah and Universitas Islam Negeri Wali Songo show moderate compliance. Health Studies has the lowest adherence, particularly in "Signage." Education Studies leads in implementing smoking prevention measures, while Social Studies effectively disseminates information about smoking dangers. This data provides insights into smoking behavior and prevalence. Conclusion: The Smoke-Free Area (SFA) implementation and adherence varied among three Islamic universities in Indonesia, with Universitas Islam Negeri Sumatera Utara showing the lowest compliance rates, while Universitas Islam Negeri Syarif Hidayatullah and Universitas Islam Negeri Wali Songo showed moderate to high adherence. Keywords: health promotion; smoke-free Area (SFA); smoking; students; university